Evaluation of spatial and temporal resolution on in situ annealing aberration-corrected transmission electron microscopy with proportional–integral–differential controller. (4th March 2019) - Shimada, Yusuke; Yoshida, Kenta; Inoue, Koji; Shiraishi, Takahisa; Kiguchi, Takanori; Nagai, Yasuyoshi; Konno, Toyohiko J
Abstract : We developed the newly in situ annealing spherical aberration corrected TEM system with propotional-integral-differential controller. The point resolution of our system was achieved 2.0 Å at 400 °C using 3 mm disk sample fabricated by ion-milling, despite of temperature fluctuation and sample drift. Abstract: The in situ annealing observation in transmission electron microscope (TEM) is one of the effective methods for imaging thermally induced microstructural changes. For applying this dynamical characterization to bulk samples fabricated by ion-milling, electro-polishing or focused ion beam (FIB) mill, it is generally needed to use a heating-pot type system. We here report an initial trial to improve the spatial and temporal resolution during the in-situ annealing observation of bulk samples using a spherical aberration corrected (AC) TEM with a new thermal control unit. The information limit of 1.5 Å and the point resolution of 2.0 Å are achieved under isothermal annealing at 350°C, which is the same resolution at room temperature, and it is affected strongly of sample drift by the temperature variation. The sample is heated at a heating rate of +1.0°C/s, the drift distance observed by a TV readout speed CCD camera is less than 2.0 Å/s.